Travailler en coopérative et dans l’économie sociale, effets sur la satisfaction et le sens du travail - Davy Castel; Claude Lemoine; Annick Durand-Delvigne (Perspectives Interdisciplinaires sur le Travail et la Santé)
This study investigates the impact of social economics on job satisfaction. According to the hypothesis, the adoption of social economics’ goals and modes of work organization is a source of job satisfaction: reduction in the separation between conception and execution, increase in work’s interest and perceived usefulness, and better cohesion and coordination among workers. Semi-structured interviews were conducted with the workers in two consulting firms in sustainable development in France, one a cooperative and the other a private company. The results of the content analysis corroborate the hypothesis. The fact that social economy’s principles have positive impacts on job satisfaction in both companies also shows that social economy’s positive influence on well-being at work depends less on formal work organization than on the meaning given to work.